2011
DOI: 10.1128/jvi.05119-11
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Single Human CD4 Domains as Potent HIV-1 Inhibitors and Components of Vaccine Immunogens

Abstract: Soluble forms of the HIV-1 receptor CD4 (sCD4) have been extensively characterized for more than 2 decades as promising inhibitors and components of vaccine immunogens. However, they were mostly based on the first two CD4 domains (D1D2), and numerous attempts to develop functional, high-affinity, stable soluble one-domain sCD4 (D1) have not been successful because of the strong interactions between the two domains. We have hypothesized that combining the power of structure-based design with sequential panning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…To briefly evaluate the nonspecificity of mD1.22 in vivo, we used a human B cell line that expresses high level of MHC-II (BJAB) and a human T cell line with no detectable MHC-II expression (SUPT1) (12). Because oligomerization of CD4 is required for a stable interaction with MHC-II (37), we generated Fc-fusion proteins of D1D2 (CD4-Ig), mD1.2 (mD1.2Fc), and mD1.22 (mD1.22Fc).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To briefly evaluate the nonspecificity of mD1.22 in vivo, we used a human B cell line that expresses high level of MHC-II (BJAB) and a human T cell line with no detectable MHC-II expression (SUPT1) (12). Because oligomerization of CD4 is required for a stable interaction with MHC-II (37), we generated Fc-fusion proteins of D1D2 (CD4-Ig), mD1.2 (mD1.2Fc), and mD1.22 (mD1.22Fc).…”
Section: Resultsmentioning
confidence: 99%
“…Several promising monomeric (3)(4)(5), dimeric (6)(7)(8), and tetrameric (9-11) sCD4 derivatives have been tested in animal models and in human clinical trials, but they exhibited modest and transient antiviral activities. Previously, we demonstrated that decreasing the molecular size of D1D2 to a single domain, D1, significantly increased its antiviral activity and reduce its nonspecificity, i.e., interactions with molecules other than the HIV-1 envelope glycoprotein (Env) gp120; a D1 variant (mD1.2) was identified that is also more soluble than D1D2 (12). However, mD1.2 still binds to human B cells and CD4 ϩ T cells without HIV-1 Env expression, although it binds more weakly than D1D2 and its stability is comparable to that of D1D2, which is relatively low (12).…”
mentioning
confidence: 99%
See 3 more Smart Citations